PENGARUH MOTIVASI BERWIRAUSAHA DAN ORIENTASI BERWIRAUSAHA TERHADAP KINERJA USAHA (Studi Pada Sektor Kuliner UMKM Kecamatan Oebobo, Kota Kupang) - Arisandy Ludia Lami, Yunengsi; E.Fanggidae, Rolland; Nursiani, Ni Putu (LPPM STIE KRAKATAU, 2024)
This research was conducted because initial observations showed that MSMEs in the area experienced fundamental symptoms that generally occur in small/medium industries, namely,there are weaknesses in the entrepreneurial field such as lack of motivation, innovation, not daring to take risks, passive, and tend to wait.Consumers who aim to determine the effect of entrepreneurship motivation and entrepreneurial orientation on business performence in culinary MSMEs in Oebobo District, Kupang City, both partially and simultaneously. The method in this study uses quantitative research and associative approach using questionnaires, interviews, observation and documentation data collection techniques, besides the population in this study is culinary MSMEs located in Oebobo District Kupang City, amounting to 117 with sample calculations carried out using the formula Taro Yamane so that 90 samples were obtained.The analysis technique in this study uses multiple linear regression using SPSS version 21 data. Hypothesis testing was carried out by t-test and F-test where before using this test, the classical assumption test was carried out. The results of the partial test show that the entrepreneurial motivation variable has a positive and significant effect on business performance, the entrepreneurial orientation variable has a positive and significant effect on the business performance of culinary MSMEs, Oebobo District Kupang City. The result of the simultaneous test show that the variables of entrepreneurial orientation have a simultaneous effect on the Business Performance of MSMEs Oebobo District Kupang City.